Extraordinary Manifestation of Evanescent Wave in Biomedical Application - Angelsky, Oleg V.; Zenkova, Claudia Yu; Hanson, Steen G.; Zheng, Jun (Frontiers in Physics, 2020)
The idea of the proposed paper is a demonstration of the evanescent wave effect on nano-objects of inorganic and organic (in particular, formed blood elements) origin localized in a biological medium, in the direction perpendicular to the direction of the Pointing vector action. On the one hand, this opens up (illustrates) new possibilities in the optical control of the direction of motion and speed of the studied nanoobjects in a layer of biological fluid. On the other hand, the very choice of objects of this type suggests the possible prospects for their use in biology, medicine, pharmacology, and precision chemistry. So, in particular, gold nanoparticles, being non-toxic to the body, are able to penetrate through the cell biomembranes, accumulate in them, thereby contributing to the diagnosis of the cell state with subsequent optical exposure to them, up to destruction in case of cancer pathologies. The role of red blood cells (RBS) in the body is generally unique and controlling their motion contributes to the complex saturation of tissues with oxygen. The choice of just the evanescent wave is explained by the need for near-surface manipulation of optical energy flows, which is especially important in the situation of studying biological complexes and structures. Exclusive manifestation of the evanescent wave action became possible under specially selected experimental condition of evanescent wave exitation. A total internal reflection was realized at the interface between the prism and a biological medium by a linearly polarized wave with the azimuth of polarization of ±45°. The result of such an excitation mechanism was a complex distribution of the optical flow density, which is accompanied by a change in the energy density both in the longitudinal direction coinciding with the direction of the wave vector and in the transverse direction perpendicular to the wave vector. The paper summarizes the latest theoretically and experimentally obtained results illustrating the rectilinear and rotational motion of investigated objects in a biological environment.